Antidiabetic and Hepatoprotective Effects of Aqueous and Ethanolic Leaf Extracts of Mitracarpus Hirtus on Alloxan-Induced Diabetic Rats - Sunday, Gabriel; Stephen, Ezeonu Chukuma; Chinedu, Imo; Tsuvini, Jonah; Attah, Atah David (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Diabetes mellitus (DM) is a metabolic disorder that remains a major health concern worldwide. It is associated with derangement of carbohydrate, protein, and lipid metabolism. This study evaluates the antidiabetic and hepatoprotective effects of aqueous and ethanolic leaf extracts of Mitracarpus hirtus on alloxan-induced diabetic rats. Fifty-five male Wistar rats were divided into 11 groups, with diabetes induced by alloxan. Treatment with aqueous and ethanolic extracts, along with Glibenclamide, lasted three weeks. At the end of the treatment period, the rats were sacrificed and blood samples were collected via cardiac puncture for biochemical analysis. Findings revealed a significant decrease (p<0.05) in fasting blood sugar (FBS) in group 10 (99.8 ± 15.74 mg/dL) when compared with group 2 (274.2 ± 7.95 mg/dL) in week 1. Week 2 also revealed a significant decrease (p<0.05) in group 11 (84.6 ± 14.98 mg/dL) when compared with group 2 (262.8 ± 15.94 mg/dL). Week 3, further revealed a significant decrease (p<0.05) in group 9 (79.4 ± 25.13 mg/dL) and group 11 (83.6 ± 8.35 mg/dL) when compared with group 2 (289.6 ± 20.89 mg/dL). Aspartate Aminotransferase (AST) revealed a significant decrease (p<0.05) when group 11 (54.38 ± 15.74 U/L) was compared with group 2 (146.66 ± 11.35 U/L). Similarly, Alanine Aminotransferase (ALT) significantly decreased (p<0.05) when group 11 (53.46 ± 4.6 U/L) was compared with group 2 (101.42 ± 16.01 U/L), while total protein and albumin increased in all treated groups. Group 5 (0.64 ± 0.11 mg/dL) in Total bilirubin (TB) had the lowest mean when compared with group 2 (2.69 ± 0.52 mg/dL). All treatment groups significantly decreased (p<0.05) Triglyceride (TG) and Cholesterol (CHOL). From this study, it has been shown that the aqueous and ethanolic leaves extracts of Mitracarpus hirtus may have the potential to ameliorate the complications due to diabetes in a dose dependent manner.